Adjusted Value Added Intellectual Coefficient and Firm Value with Good Corporate Governance as a Moderator : Evidences from Commercial and Sharia Banking in Indonesia - Ayu Triani, Niken; Dian, Ririh (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study was to investigate the relationship between intellectual capital and firm value in commercial and sharia banks in Indonesia using good corporate governance as a moderator. This review included commercial and sharia banks still up in the air by the creator recorded on the Indonesia Stock Trade (IDX) from the period 2018 to the period 2021, utilizing the Directed Relapse Examination (MRA) technique which is checked on from the fiscal summaries, by delivering 17 organizations as an example and tried utilizing with SPSS. The results obtained from the examination demonstrate the way that intellectual capital can have a significant effect on firm value and good corporate governance as a moderator can significantly strengthen the impact of intellectual capital on firm value, utilizing the A-VAIC model as an estimation. In order for commercial and sharia banks in Indonesia to increase the firm value, they need to develop an efficient method for fully disclosing intellectual capital, supported by the existence of good corporate governance as an efficient system that will attract stakeholders' attention. This study used the A-VAIC (Adjusted Value Added Intellectual Coefficient) as a measurement of intellectual capital efficiency.